Reply: Bias in literature search and national scientifi c production in health human resources - Romaní Romaní, Franco (2017)
Mr. Editor We consider important the observation and contribution made regarding the scientific production in Human Resources in Health in Peru. The study in reference had as one of its objectives to characterize the scientific production around the national research agenda on Human Resources in Health (period 2011-2014). This agenda included 30 specific research topics grouped in two areas: health education and health work (1). The search strategies employed used the descriptors called Medical Subject Headings (MeSH) for the SCOPUS database and the descriptors in Health Sciences (DeCS) for the LILACS database. In this last structured vocabulary, the descriptors related to Human Resources in Health are 'Human Resources in Health' and 'Personal Health', which were used in the construction of our search strategy.